Is the J-Curve a Reality in Developing Countries? - HUSSAIN, M. Ershad; HAQUE, Mahfuzul (Journal of Economics and Political Economy, 2014)
We examine the relationship between trade balance and net export with both, the official and real effective exchange rates on the J-Curve hypothesis and find evidence to support in favor of the hypothesis, coming from a panel data of 49 developing countries from Africa. Countries can improve their current account balance by depreciating their currency; however the J-curve hypothesis argues that such changes take time to occur, but should use exchange rate policies discreetly, as it belongs to the “beggar thy neighbor” policies. This may be good for home country but is not so good for the foreign country; as a result, such policies may trigger retaliatory policies. Restrictive trade policies are against the present day notion of free-economy and free-trade policy these are very common around the world.